Lithium ion battery positive electrode material, precursor and preparation method thereof, lithium ion battery and lithium battery equipment

By controlling the crystal plane ratios and reaction conditions, the lithium-ion battery precursor achieves improved electrochemical stability and capacity performance through enhanced crystallinity and consistent primary particle morphology, addressing the challenges of cycle and capacity limitations in existing materials.

CN119230812APending Publication Date: 2024-12-31HUNAN ZOOMWE NEW ENERGY TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310799087.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing lithium-ion battery positive electrode materials made from medium-high nickel precursors face challenges in achieving both high cycle performance and high capacity due to variations in crystal structure and primary particle forms, leading to material fracture and poor contact between active particles, which affects battery performance.

Method used

The development of a lithium-ion battery positive electrode material precursor with specific crystal plane ratios, primary particle shapes, and controlled reaction conditions to enhance crystallinity and consistency, ensuring the (100) crystal plane dominance and inhibiting the (001) crystal plane growth, resulting in improved cycle and capacity performance.

Benefits of technology

The solution provides a lithium-ion battery with enhanced electrochemical stability, capacity, and cycle performance by maintaining the integrity of the material structure under pressure and during charging and discharging, thereby improving the battery's overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230812A_ABST
    Figure CN119230812A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery positive electrode material, a precursor, a preparation method of the precursor, a lithium ion battery and lithium battery equipment, and relates to the field of lithium ion batteries. The secondary particles of the precursor comprise a plurality of strip-shaped or shuttle-shaped primary particles, and the ratio of the grain size D (100) / D (001) of the precursor is 1.50-2.40. The preparation method comprises the following steps: adding raw materials including a metal salt solution, a precipitator and a complexing agent into a base solution, reacting according to a preset procedure, and adjusting the pH value in the reaction process until a crystal nucleus is obtained; the method comprises the following steps: adding materials including a metal salt solution, a precipitator, a complexing agent and a crystal nucleus into a base solution, reacting according to a preset procedure, and adjusting the pH value in the reaction process. The raw material of the lithium ion battery positive electrode material comprises a lithium ion battery positive electrode material precursor. The precursor provided by the invention gives consideration to both capacity performance and cycle performance by inhibiting growth of a (001) plane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium-ion batteries, and in particular to a lithium-ion battery positive electrode material, a precursor and a preparation method thereof, a lithium-ion battery and a lithium battery device. Background Art

[0002] With the rapid development of the power battery market and the arrival of the first and second batches of large-scale battery replacement for new energy electric vehicles, end users are increasingly concerned about the cycle life of power batteries due to the high prices of power batteries. In addition, in order to reduce the number of charging times and charging time during travel, end users have also been constantly making new requirements for batteries with long battery life and high energy density.

[0003] As one of the four core materials of the battery, the positive electrode material restricts the comprehensive performance of the battery, while the precursor material, as the raw material of the positive electrode material, determines the performance of the final material.

[0004] Medium-high nickel precursors have high nickel content and excellent properties such as high capacity and high battery energy density. At the same time, nickel can replace cobalt to reduce costs, and the market demand is growing. During the preparation process of the medium-high nickel precursors currently prepared, the growth advantages of the (001) crystal plane, (100) crystal plane, and (101) crystal plane are different, resulting in differences in crystal structure, which affects the electrochemical performance. At the same time, the primary particles of the medium-high nickel precursor have different forms such as blocks, strips, shuttles, and flakes. The primary particles of different forms and arrangements have different probabilities and degrees of rupture when under pressure or charging and discharging, which affects the cycle performance.

[0005] In the article "Analysis and Improvement of Cycle Attenuation of High Nickel Ternary Lithium-ion Batteries", Zhang Xin, Kong Lingli, Gao Tengyue and others took NCM811 / graphite system cells as the research object and conducted charge and discharge cycle tests at 45°C. During the high-temperature cycle, the integrity of the material's layered structure was significantly weakened, and the crystal structure was damaged, which hindered the migration of lithium ions and led to cycle failure. And SEM electron microscope photos show that large areas of obvious microcracks and even cracks appeared in the positive electrode material after the cycle, and the material after high-temperature cycle showed serious powdering. This is mainly because during the repeated charge and discharge process, the unit cell continues to expand and contract, resulting in the fracture and powdering of the positive electrode material particle structure, resulting in poor contact between active particles, increasing the internal resistance of the battery, and the increase in the specific surface area of ​​the material, which aggravates the side reaction with the electrolyte and causes the material to fail.

[0006] How to quickly screen out products that meet both high cycle performance and high capacity performance from a wide variety of medium and high nickel precursor materials through quantifiable parameters is one of the problems that the industry needs to solve urgently. At the same time, how to prepare the above-screened products that meet both high cycle performance and high capacity performance is also one of the problems that the industry needs to solve urgently. Summary of the invention

[0007] The purpose of the present application is to provide a lithium-ion battery positive electrode material, a precursor and a preparation method thereof, a lithium-ion battery and a lithium battery device to solve the above-mentioned problems.

[0008] To achieve the above objectives, this application adopts the following technical solutions:

[0009] A lithium-ion battery positive electrode material precursor, wherein the secondary particles of the precursor include a plurality of primary particles in strip or shuttle shapes, and the precursor satisfies formula 1:

[0010] Formula 1: 1.50≤D (100) / D (001) ≤2.40,

[0011] In formula 1, D (100) is the grain size in the (100) crystal plane, D (001) is the grain size in the (001) crystal plane.

[0012] Preferably, the lithium-ion battery cathode material precursor satisfies at least one of the following conditions:

[0013] (1) The precursor satisfies formula 2,

[0014] Formula 2: 2.10≤D (100) / D (001) ≤2.30;

[0015] (2) The precursor satisfies formula 3,

[0016] Formula 3: 2.00≤D (101) / D (001) ≤2.90,

[0017] In formula 3, D (101) is the grain size in the (101) crystal plane, D (001) is the grain size in the (001) crystal plane;

[0018] Preferably, the precursor satisfies Formula 4,

[0019] Formula 4: 2.30≤D (101) / D (001) ≤2.70;

[0020] (3) The half maximum width (FWHM) (101) of the precursor on the (101) crystal plane is 0.50°-0.65°;

[0021] (4) Diffraction peak intensity I of the precursor on the (101) crystal plane (101) The diffraction peak intensity I (001) Ratio I (101) / I (001)is 0.97 - 1.10;

[0022] (5) The number of (101) wafers of the precursor is N (101) is 50 - 80, N (101) = D (101) / d (101) where d (101) represents the interplanar spacing of the (101) crystal plane;

[0023] Specifically, D (101) = kλ / [βcosθ (101) ,

[0024] d (101) = nλ / 2sinθ (101) = 0.23,

[0025] Then, N (101) = D (101) / d (101) = kλ / [0.23βcosθ (101) , where k is the Scherrer constant 0.89;

[0026]

[0027] β is the FWHM (101) full width at half maximum;

[0028] Preferably, the number of (101) wafers of the precursor is N (101) is 60 - 70.

[0029] Preferably, the precursor of the lithium-ion battery cathode material satisfies at least one of the following conditions:

[0030] ① The average value of the absolute value of the relative deviation of the length of the primary particles |Ma| ≤ 40%, and the average value of the absolute value of the relative deviation of the width of the primary particles |Mb| ≤ 40%,

[0031] where

[0032] a is the length of the primary particle, and b is the width of the primary particle,

[0033] is the average length of the primary particles, and b is the average width of the primary particles,

[0034] Specifically,

[0035] where

[0036] a1, a2, a3, a n are respectively the lengths of the 1st, 2nd, 3rd, and nth primary particles, and b1, b2, b3, b nare the widths of the 1st, 2nd, 3rd, and nth primary particles respectively;

[0037] |Ma| and |Mb| are calculated by formula ① and formula ② respectively,

[0038]

[0039]

[0040] Specifically,

[0041] The average value of |Ma| = (|Ma1| + |Ma2| + |Ma3| +..... |Ma n |) / n, and the average value of |Mb| = (|Mb1| + |Mb2| + |Mb3| +..... |Mb n |) / n; where,

[0042] |Ma1|, |Ma2|, |Ma3|, |Ma n | are the absolute values of the relative deviations of the lengths of the 1st, 2nd, 3rd, and nth primary particles respectively;

[0043] |Mb1|, |Mb2|, |Mb3|, |Mb n | are the absolute values of the relative deviations of the widths of the 1st, 2nd, 3rd, and nth primary particles respectively;

[0044] ② The precursor includes primary particles satisfying 300nm ≤ a ≤ 1200nm and 50nm ≤ b ≤ 200nm;

[0045] Preferably, 500nm ≤ a ≤ 1000nm and 50nm ≤ b ≤ 100nm.

[0046] Preferably, the precursor of the lithium-ion battery cathode material satisfies at least one of the following conditions:

[0047] A. The chemical general formula of the precursor is Ni x M 1-x (OH)2, where 0 ≤ x < 1 and M is at least one of Co, Mn, Al, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb, or Sr;

[0048] Preferably, 0.6 ≤ x < 1;

[0049] B. The chemical general formula of the precursor is Ni y Co z M 1 w M 2 v(OH)2, where 0≤y<1, 0≤z<0.6, y+z+w+v=1; M 1 is Mn and / or Al; M 2 At least one of Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb or Sr;

[0050] Preferably, 0.6≤y<1;

[0051] C. The particle size D50 of the secondary particles of the precursor is 8-22 μm;

[0052] D. The specific surface area of ​​the precursor is 8-20m 2 / g;

[0053] Preferably, the BET surface area of ​​the precursor is 10-15 m 2 / g;

[0054] E. The tap density TD of the precursor is 1.8-2.1g / cm 3 ;

[0055] F. The primary particles in the precursor are arranged in a disordered manner.

[0056] The present application also provides a method for preparing a lithium-ion battery positive electrode material precursor, comprising:

[0057] Adding raw materials including a metal salt solution, a precipitant, and a complexing agent into a first base solution, and performing a first reaction according to a first predetermined procedure until a crystal nucleus is obtained;

[0058] Adding materials including a metal salt solution, a precipitant, a complexing agent, and crystal nuclei into a second base liquid, and performing a second reaction according to a second predetermined procedure until a precursor is obtained;

[0059] Wherein, the first base liquid and the second base liquid independently include water, a precipitant and a complexing agent.

[0060] Preferably, the method for preparing a lithium-ion battery positive electrode material precursor satisfies at least one of the following conditions:

[0061] a. The first predetermined procedure includes: after the first reaction starts, gradually reducing the pH value during the first reaction, and maintaining the final pH value of the first reaction in the range of 9-11;

[0062] b. The second predetermined procedure includes: after the second reaction starts, adjusting the pH value of the second reaction, and maintaining the final pH of the second reaction in the range of 10-12.

[0063] Preferably, the method for preparing a lithium-ion battery positive electrode material precursor satisfies at least one of the following conditions:

[0064] c. The particle size D50 of the crystal nucleus is 3-10 μm;

[0065] d. The pH of the first base liquid and the second base liquid are independently 10-12, and the ammonia concentration of the first base liquid and the second base liquid are independently 1-15 g / L;

[0066] e. During the first reaction, the flow rate of the metal salt solution is 1-5% / h of the available volume of the reaction container, the flow rate of the precipitant is 0.35-1.85% / h of the available volume of the reaction container, and the flow rate of the complexing agent is 0.03-0.15% / h of the available volume of the reaction container;

[0067] f. During the second reaction, the flow rate of the metal salt solution is 1-5% / h of the available volume of the reaction vessel, the flow rate of the precipitant is 0.35-1.85% / h of the available volume of the reaction vessel, and the flow rate of the complexing agent is 0.03-0.15% / h of the available volume of the reaction vessel;

[0068] g. The temperature of the first reaction and the second reaction is independently 60-80°C;

[0069] h. The mother liquor is continuously discharged during the first reaction and the second reaction, and the discharge amount is equal to the total feed amount;

[0070] i. After the second reaction is completed, post-processing is also included: the product of the second reaction is subjected to solid-liquid separation, drying, and sieving for demagnetization.

[0071] The present application also provides a lithium-ion battery positive electrode material, and the raw materials of the positive electrode material include a lithium-ion battery positive electrode material precursor.

[0072] The present application also provides a lithium-ion battery, which includes a lithium-ion battery positive electrode material.

[0073] The present application also provides a lithium battery device, including a lithium-ion battery.

[0074] Compared with the prior art, the beneficial effects of this application include:

[0075] The primary particles in the lithium-ion battery positive electrode material precursor provided in the present application are strip-shaped or shuttle-shaped, which have better pressure bearing capacity than thin sheets. The positive electrode material inheriting this structure is not easy to break when under pressure or when charging and discharging, which can improve the battery cycle performance. The present application also defines the grain size D based on the characterization data calculated based on the XRD data. (100) / D (001) ratio, because the (001) crystal plane of the precursor will be converted into the (003) crystal plane of the positive electrode active material after sintering, which is thermodynamically stable and electrochemically inert, which is not conducive to the transmission of lithium ions. +In order to improve the transmission path and deintercalation speed of the precursor, it is necessary to inhibit the growth of the corresponding precursor (001) crystal plane, make the (100) crystal plane the dominant crystal plane, inhibit the grain size of the (001) crystal plane, and increase the grain size of the (100) crystal plane, thereby improving the battery capacity. (100) / D (001) , so that the battery prepared with the corresponding positive electrode material has both cycle performance and capacity performance.

[0076] The present application also provides a method for preparing a precursor of a positive electrode material for a lithium-ion battery. By controlling the pH value of the first reaction and the second reaction, the primary particles in the obtained precursor have (100) and (101) crystal planes as the dominant crystal planes, have a high degree of crystallinity, and the primary particle morphology has a high degree of consistency, so that the precursor has excellent electrochemical properties. The present application also controls the reaction temperature and reacts at high temperatures to improve the crystallinity and crystallization rate of the product. The former improves the product crystallinity and can improve the product's cycle performance, and the latter improves the crystallization rate and can improve the product production rate.

[0077] The lithium-ion battery positive electrode material, lithium-ion battery and lithium battery equipment provided in the present application have good electrochemical stability and excellent capacity and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0078] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0079] Figure 1 This is a schematic diagram of primary particle consistency comparison;

[0080] Figure 2 This is a partial SEM magnified photograph of the surface of the secondary particles of the lithium-ion battery positive electrode material precursor obtained in Example 1;

[0081] Figure 3 The XRD curve of the positive electrode material precursor of lithium ion battery obtained in Example 1;

[0082] Figure 4 This is a partial SEM magnified photograph of the surface of the secondary particles of the lithium-ion battery positive electrode material precursor obtained in Example 2;

[0083] Figure 5 The XRD curve of the positive electrode material precursor of lithium ion battery obtained in Example 2;

[0084] Figure 6 This is a partial SEM magnified photograph of the surface of the secondary particles of the lithium-ion battery positive electrode material precursor obtained in Example 3;

[0085] Figure 7 The XRD curve of the positive electrode material precursor of lithium ion battery obtained in Example 3;

[0086] Figure 8 This is a partial SEM magnified photograph of the surface of the secondary particles of the lithium-ion battery positive electrode material precursor obtained in Comparative Example 1;

[0087] Fig. 9 This is the XRD curve of the lithium-ion battery positive electrode material precursor obtained in Comparative Example 1;

[0088] Fig.10 This is a partial SEM magnified photograph of the surface of the secondary particles of the lithium-ion battery positive electrode material precursor obtained in Comparative Example 2;

[0089] Fig.11 This is the XRD curve of the lithium-ion battery positive electrode material precursor obtained in Comparative Example 2. DETAILED DESCRIPTION

[0090] As used herein:

[0091] As used herein, the term "comprise" or any other variation thereof is intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0092] When concentration, or other values ​​or parameters are expressed as ranges, preferred ranges, or a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0093] In these examples, parts and percentages are by mass unless otherwise specified.

[0094] A lithium-ion battery positive electrode material precursor, wherein the secondary particles of the precursor include a plurality of primary particles in a strip or shuttle shape, the secondary particles of the precursor include a plurality of primary particles in a strip or shuttle shape, and the precursor satisfies formula 1,

[0095] Formula 1: 1.50≤D (100) / D (001) ≤2.40,

[0096] In formula 1, D (100) is the grain size in the (100) crystal plane, D (001) is the grain size in the (001) crystal plane.

[0097] Optionally, D (100) / D (001) The ratio can be 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30 or 2.40, or any value between 1.50 and 2.40.

[0098] The morphology of the primary particles is strip-shaped or shuttle-shaped, not flake-shaped, and has a certain thickness. The positive electrode material inheriting this structure is not easy to break when under pressure or when charging and discharging, which can improve the battery cycle performance.

[0099] Grain size ratio D (100) / D (001) It can be calculated by the following formula:

[0100]

[0101] Among them, the diffraction angle 2θ corresponding to the (001) crystal plane is 19.2±1°; the diffraction angle 2θ corresponding to the (100) crystal plane is 33.0±1°;

[0102] FWHM(001) is the half-peak width of the (001) crystal plane corresponding to the precursor, and FWHM(100) is the half-peak width of the (100) crystal plane corresponding to the precursor.

[0103] The crystals inside the precursor primary particles have (001) crystal plane, (100) crystal plane, (101) crystal plane, etc. + The transmission path and deintercalation speed determine the performance of the material capacity. The (001) crystal plane of the precursor will be converted into the (003) crystal plane of the positive electrode active material after sintering. However, the (003) crystal plane of the positive electrode active material is thermodynamically stable and electrochemically inert, so it is not conducive to the transmission of lithium ions. In order to improve Li + In order to reduce the mobility of other crystal planes, it is necessary to inhibit the growth of the corresponding precursor (001) crystal plane, thereby reducing the grain size of the (001) crystal plane and improving the capacity performance. (100) / D (001) , taking into account both cycle performance and capacity performance.

[0104] Preferably, the lithium-ion battery cathode material precursor satisfies at least one of the following conditions:

[0105] (1) The precursor satisfies formula 2,

[0106] Formula 2: 2.10≤D (100) / D (001) ≤2.30;

[0107] (2) The precursor satisfies formula 3,

[0108] Formula 3: 2.00≤D (101) / D (001) ≤2.90,

[0109] In formula 3, the diffraction angle corresponding to the (101) crystal plane is 2θ = 19.2 ± 1°; D (101) is the grain size in the (101) crystal plane, D (001) is the grain size in the (001) crystal plane;

[0110] Preferably, the precursor satisfies Formula 4,

[0111] Formula 4: 2.30≤D (101) / D (001) ≤2.70;

[0112] Optionally, D (101) / D (001) The ratio can be 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80 or 2.90, or any value between 2.00 and 2.90.

[0113] (3) The half maximum width (FWHM) (101) of the precursor on the (101) crystal plane is 0.50°-0.65°;

[0114] Among them, I (101) I is the peak intensity of the (101) crystal plane corresponding to the diffraction angle 2θ = 39.0 ± 1° in the precursor; (001) The precursor has a peak intensity of the (001) crystal plane corresponding to the diffraction angle 2θ = 19.2±1°.

[0115] Optionally, the half maximum width FWHM (101) of the precursor in the (101) crystal plane can be 0.50°, 0.51°, 0.52°, 0.53°, 0.54°, 0.55°, 0.56°, 0.57°, 0.58°, 0.59°, 0.60°, 0.61°, 0.62°, 0.63°, 0.64° or 0.65°, or any value between 0.50° and 0.65°.

[0116] (4) Diffraction peak intensity I of the precursor on the (101) crystal plane (101) The intensity of the diffraction peak of the (001) crystal plane is (001) Ratio I (101) / I (001)0.97-1.10;

[0117] Optionally, the diffraction peak intensity I of the precursor on the (101) crystal plane (101) The intensity of the diffraction peak of the (001) crystal plane is (001) Ratio I (101) / I (001) can be 0.97, 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.10 or any value between 0.97 and 1.10;

[0118] By further limiting the precursor D (100) / D (001) , D (101) / D (001) , FWHM(101), peak intensity ratio I (101) / I (001) , a specific crystal structure is obtained, which can take into account both battery cycle and capacity performance.

[0119] (5) The number of precursor wafers N(101) is 50-80, N (101) =D (101) / d (101) , d (101) represents the interplanar spacing of the (101) crystal plane;

[0120] Specifically, D (101) = kλ / [βcosθ (101) ],

[0121] d (101) = = nλ / 2sinθ (101) =0.23,

[0122] Then, from N(101)=D (101) / d (101) =kλ / [0.23βcosθ(101)],

[0123] Preferably, the number of precursor (101) wafers N(101) is 60-70.

[0124] Where k is the Scherrer constant 0.89;

[0125]

[0126] β is the half-peak width (FWHM) (101).

[0127] Optionally, the number of (101) wafers of the precursor can be 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80 or any positive integer between 50 and 80.

[0128] Li + The transmission path and the deintercalation rate of Li determine the performance of the material capacity. When the precursor material preferentially grows along the (101) crystal plane and the number of (101) wafers is small, the transmission path of the sintered cathode material on the transformed crystal plane is short, which is beneficial to the performance of the capacity; however, when the number of (101) wafers is too small, the crystal tends to grow on the (001) crystal plane, thus affecting the transmission of lithium ions on the corresponding crystal plane of the inherited cathode material and being unfavorable to the performance of the capacity.

[0129] The number of (101) wafers within a specific range can ensure the deintercalation rate of lithium ions on the (101) crystal plane, taking into account the diffusion transmission and insertion / deintercalation of lithium ions in the cathode material, thereby enabling the capacity to be exerted. The smaller the number of (101) wafer layers within a specific range, the higher its capacity; the larger the number of its wafer layers, the better the cycle performance.

[0130] Preferably, the precursor of the lithium ion battery cathode material satisfies at least one of the following conditions:

[0131] ① The average value of the absolute value of the relative deviation |Ma| of the length of the primary particles ≤ 40%, and the average value of the absolute value of the relative deviation |Mb| of the width of the primary particles ≤ 40%.

[0132] In the local SEM image of the surface, select the complete primary particles and screen out the incomplete primary particles at the edge of the image. Measure the longest length a and the widest width b of each primary particle to obtain the ranges of the length a and the width b respectively; then calculate the average length a and the average width b, and finally calculate the average value of the absolute value of the relative deviation |Ma| of the length and the average value of the absolute value of the relative deviation |Mb| of the width.

[0133] Among them,

[0134] a is the length of the primary particle, b is the width of the primary particle.

[0135] a is the average length of the primary particles, b is the average width of the primary particles. Specifically, a = (a1 + a2 + a3 +...... + a n ) / n, b = (b1 + b2 + b3 +...... + b n ) / n;

[0136] Among them,

[0137] a1, a2, a3, a n are respectively the lengths of the 1st, 2nd, 3rd, and nth selected primary particles, and b1, b2, b3, b n are respectively the widths of the 1st, 2nd, 3rd, and nth selected primary particles;

[0138] |Ma| and |Mb| are respectively calculated by formula ① and formula ②,

[0139]

[0140]

[0141] Specifically,

[0142] The average value of |Ma| = (|Ma1| + |Ma2| + |Ma3| +..... |Ma n |) / n, and the average value of |Mb| = (|Mb1| + |Mb2| + |Mb3| +..... |Mb n |) / n; where,

[0143] |Ma1|, |Ma2|, |Ma3|, |Ma n | are respectively the absolute values of the relative deviations of the lengths of the 1st, 2nd, 3rd, and nth primary particles;

[0144] |Mb1|, |Mb2|, |Mb3|, |Mb n | are respectively the absolute values of the relative deviations of the widths of the 1st, 2nd, 3rd, and nth primary particles;

[0145] A small average value of the relative deviation indicates good consistency of the primary particles. The primary particles of the cathode material inheriting this morphology also have good morphology consistency, thus avoiding problems such as fracture at the joints between different primary particles and surface cracks of the particles caused by different stress states during charge and discharge, thereby improving the cycling performance.

[0146] Optionally, the average value of the absolute value of the relative deviation of the length of the primary particle |Ma| and the average value of the absolute value of the relative deviation of the width of the primary particle |Mb| can each independently be 0, 10%, 20%, 30%, 40% or any value between greater than or equal to 0 and less than or equal to 40%.

[0147] ② The precursor includes primary particles satisfying 300nm ≤ a ≤ 1200nm and 50nm ≤ b ≤ 200nm;

[0148] Preferably, 500nm ≤ a ≤ 1000nm and 50nm ≤ b ≤ 100nm.

[0149] By limiting the average length and average width range of primary particles, primary particles with large size differences can be screened out to obtain products with suitable specific surface area and tap density, properly balancing the capacity and cycle performance of the battery. Although primary particles that are too fine can provide abundant pores between the primary particles, which is beneficial to the embedding and deintercalation of lithium ions, and the battery prepared with the positive electrode material has a higher capacity, it is easy to break, resulting in poor cycle performance. On the contrary, primary particles that are too coarse tend to be densely arranged, with a reduced number of surface pores, a lower capacity, and better cycle performance. By limiting the length and width range of primary particles, the capacity and cycle performance of the battery can be properly balanced. Figure 1 As shown, the preferred embodiment of primary particles of type A, type B, and type C is: A>C>B.

[0150] Optionally, the precursor includes primary particles satisfying the average length a of 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm or any value between 300-1200nm, and the average width b of the primary particles is 50nm, 100nm, 150nm, 200nm or any value between 50-200nm.

[0151] In an optional embodiment, the positive electrode material of the lithium ion battery satisfies at least one of the following conditions:

[0152] A. The chemical formula of the precursor is Ni x M 1-x (OH)2, wherein 0≤x<1, and M is at least one of Co, Mn, Al, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb or Sr;

[0153] Preferably, 0.6≤x<1;

[0154] Optionally, x can be 0, 0.01, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 0.99 or any value greater than or equal to 0 and less than 1.

[0155] B. The chemical formula of the precursor is Ni y Co z M 1 w M 2 v (OH)2, where 0≤y<1, 0≤z<0.6, y+z+w+v=1; M 1is Mn and / or Al; M 2 At least one of Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb or Sr;

[0156] Preferably, 0.6≤y<1;

[0157] Optionally, y can be 0, 0.01, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 0.99 or any value greater than or equal to 0 and less than 1; z can be 0, 0.01, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.59 or any value greater than or equal to 0 and less than 0.6.

[0158] The lithium-ion battery positive electrode material precursor provided in the present application can be a binary precursor material or a ternary precursor material.

[0159] C. The particle size D50 of the secondary particles of the precursor is 8-22 μm;

[0160] D. The specific surface area of ​​the precursor is 8-20m 2 / g;

[0161] Preferably, the BET surface area of ​​the precursor is 10-15 m 2 / g;

[0162] E. The tap density TD of the precursor is 1.8-2.1g / cm 3 .

[0163] Optionally, the particle size D50 of the secondary particles of the precursor can be 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm or any value between 8 and 22 μm; the BET specific surface area of ​​the precursor can be 8 m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g or 8-20m 2 / g; the tap density TD of the precursor can be 1.8g / cm 3 , 1.85g / cm 3 , 1.9g / cm 3 , 1.95g / cm 3 , 2.0g / cm 3 , 2.05g / cm 3 , 2.1g / cm 3 or 1.8-2.1g / cm 3 Any value in between.

[0164] Under the same conditions, particle size is positively correlated with tap density. The larger the particle size, the greater the tap density. Tap density can increase the compaction density of the cathode material that inherits the precursor, increase energy density, and thus increase battery capacity.

[0165] The specific surface area is tested by nitrogen adsorption. The larger the specific surface area, the more pores there are in the precursor. Rich pores are conducive to increasing the contact area between the positive electrode material and the electrolyte after sintering, accelerating the electrochemical reaction rate, and improving the battery capacity performance. However, too high a specific surface area may cause too many pores in the material, which may break when under pressure or break due to stress changes during charging and discharging, thereby affecting the cycle performance.

[0166] In summary, by limiting the particle size, tap density, and specific surface area, both the capacity and cycle of the battery can be taken into account.

[0167] F. The primary particles in the precursor are arranged in a disordered manner;

[0168] The primary particles of the secondary particle spheres are arranged in a disordered manner, which can increase the distance between the primary particles while keeping the length and width of the primary particles unchanged, and increase the number of pores on the surface of the secondary particle spheres, which is beneficial to the embedding and de-embedding of lithium salts and improves the battery capacity.

[0169] The present application also provides a method for preparing a lithium-ion battery positive electrode material precursor, comprising:

[0170] Adding raw materials including a metal salt solution, a precipitant, and a complexing agent into a first base solution, and performing a first reaction according to a first predetermined procedure until a crystal nucleus is obtained;

[0171] Adding materials including a metal salt solution, a precipitant, a complexing agent, and crystal nuclei into a second base liquid, and performing a second reaction according to a second predetermined procedure until a precursor is obtained;

[0172] Wherein, the first base liquid and the second base liquid independently include water, a precipitant and a complexing agent.

[0173] In an optional embodiment, the method for preparing a lithium-ion battery positive electrode material precursor satisfies at least one of the following conditions:

[0174] a. The first predetermined procedure includes: after the first reaction starts, gradually reducing the pH value during the first reaction, and maintaining the final pH value of the first reaction in the range of 9-11;

[0175] Optionally, the final pH value of the first reaction is maintained at 9, 9.5, 10, 10.5, 11 or any value in the range of 9-11;

[0176] b. The second predetermined procedure includes: after the second reaction starts, adjusting the pH value of the second reaction, and maintaining the final pH of the second reaction in the range of 10-12.

[0177] Optionally, the final pH of the second reaction is maintained at 10, 10.5, 11, 11.5, 12 or any value within the range of 10-12.

[0178] Preferably, the method for preparing a lithium-ion battery positive electrode material precursor satisfies at least one of the following conditions:

[0179] c. The particle size D50 of the crystal nucleus is 3-10 μm;

[0180] Optionally, the particle size D50 of the crystal nucleus may be 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or any value between 3 and 10 μm;

[0181] d. The pH of the first base liquid and the second base liquid are independently 10-12, and the ammonia concentration of the first base liquid and the second base liquid are independently 1-15 g / L;

[0182] Optionally, the pH of the first base liquid and the second base liquid can be 10, 10.5, 11, 11.5, 12 or any value between 10-12, and the ammonia concentration of the first base liquid and the second base liquid can be 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L, 15 g / L or any value between 1-15 g / L;

[0183] e. During the first reaction, the flow rate of the metal salt solution is 1-5% / h of the available volume of the reaction container, the flow rate of the precipitant is 0.35-1.85% / h of the available volume of the reaction container, and the flow rate of the complexing agent is 0.03-0.15% / h of the available volume of the reaction container;

[0184] Optionally, during the first reaction, the flow rate of the metal salt solution can be 1% / h, 2% / h, 3% / h, 4% / h, 5% / h or any value between 1-5% / h of the available volume of the reaction container, and the flow rate of the precipitant can be 0.35% / h, 0.50% / h, 1.00% / h, 1.50% / h, 1.85% / h or any value between 0.35-1.85% / h of the available volume of the reaction container. any value, the flow rate of the complexing agent can be 0.03% / h, 0.04% / h, 0.05% / h, 0.06% / h, 0.07% / h, 0.08% / h, 0.09% / h, 0.10% / h, 0.11% / h, 0.12% / h, 0.13% / h, 0.14% / h, 0.15% / h or any value between 0.03-0.15% / h of the available volume of the reaction vessel;

[0185] f. During the second reaction, the flow rate of the metal salt solution is 1-5% / h of the available volume of the reaction vessel, the flow rate of the precipitant is 0.35-1.85% / h of the available volume of the reaction vessel, and the flow rate of the complexing agent is 0.03-0.15% / h of the available volume of the reaction vessel;

[0186] Optionally, during the second reaction, the flow rate of the metal salt solution can be 1% / h, 2% / h, 3% / h, 4% / h, 5% / h or any value between 1-5% / h of the available volume of the reaction container, and the flow rate of the precipitant can be 0.35% / h, 0.50% / h, 1.00% / h, 1.50% / h, 1.85% / h or any value between 0.35-1.85% / h of the available volume of the reaction container. any value, the flow rate of the complexing agent can be 0.03% / h, 0.04% / h, 0.05% / h, 0.06% / h, 0.07% / h, 0.08% / h, 0.09% / h, 0.10% / h, 0.11% / h, 0.12% / h, 0.13% / h, 0.14% / h, 0.15% / h or any value between 0.03-0.15% / h of the available volume of the reaction vessel;

[0187] g. The temperature of the first reaction and the second reaction is independently 60-80°C;

[0188] Optionally, the temperature of the first reaction and the second reaction can be independently 60°C, 65°C, 70°C, 75°C, 80°C or any value between 60-80°C;

[0189] h. The mother liquor is continuously discharged during the first reaction and the second reaction, and the discharge amount is equal to the total feed amount;

[0190] i. After the second reaction is completed, post-processing is also included: the product of the second reaction is subjected to solid-liquid separation, drying, and screening for demagnetization.

[0191] The present application also provides a lithium-ion battery positive electrode material, and the raw materials of the positive electrode material include a lithium-ion battery positive electrode material precursor.

[0192] The present application also provides a lithium-ion battery, which includes a lithium-ion battery positive electrode material.

[0193] The present application also provides a lithium battery device, including a lithium-ion battery.

[0194] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0195] Example 1

[0196] This embodiment provides a lithium ion battery positive electrode material precursor, and the preparation method thereof is as follows:

[0197] Step 1: Calculate and weigh nickel sulfate crystals, cobalt sulfate crystals, and manganese sulfate crystals, and prepare a metal salt solution with a total metal molar amount of 2 mol / L according to the metal molar ratio of nickel, cobalt, and manganese of 88.5:8:3.5;

[0198] Step 2: Add pure water, sodium hydroxide solution and ammonia water into the reactor, stir evenly at 220 r / min, keep the temperature at 60° C., and obtain a first bottom solution with a pH value of 11.5 and an ammonia concentration of 4.5 g / L;

[0199] Step 3, the metal salt solution, sodium hydroxide solution, and ammonia water are simultaneously introduced into the reactor that has been added to the bottom liquid at a flow rate of 2.0-2.1% / h, 0.7-1.0% / h, and 0.06-0.08% / h of the available reactor volume, respectively, and the temperature is kept at 60°C. After the reaction precipitation begins, the pH is gradually reduced by adjusting the liquid alkali flow rate and finally maintained in the range of 10.8-11.0. During the reaction, the mother liquor is discharged through the concentration equipment, and the discharge rate is consistent with the total feed amount; until the nickel-cobalt-manganese precipitation nucleus with a medium particle size D50 of 5.1μm is obtained and dehydrated;

[0200] Step 4: Put the dehydrated nickel-cobalt-manganese crystal nuclei obtained in step 3 into a reactor, add water, sodium hydroxide solution and ammonia water to obtain a second bottom liquid with a pH value of 10.8 and an ammonia concentration of 3.7 g / L. The metal salt solution, sodium hydroxide solution and ammonia water are continuously introduced into the reactor at a flow rate of 2.0-2.1% / h, 0.7-1.0% / h and 0.06-0.08% / h of the available reactor volume, respectively, and the temperature is kept at 75°C. After the reaction precipitation begins, the pH is gradually reduced to 10.6 by adjusting the liquid alkali flow rate, and then the pH is gradually increased and finally maintained at a value of 11.1-11.3. During the reaction, the mother liquor is discharged through the concentration equipment, and the discharge rate is consistent with the total feed amount; until a nickel-cobalt precipitate with a D50 of 11.0 μm is obtained.

[0201] Step 5: Wash, centrifuge, dry, and sieve the reaction precipitate slurry to remove magnetism, and obtain a lithium-ion battery positive electrode material precursor with the chemical formula of Ni 0.885 Co 0.08 Mn 0.035 (OH)2.

[0202] The SEM partial magnified photo of the surface of the secondary particles of the obtained lithium-ion battery positive electrode material precursor is as follows: Figure 2 As shown, the XRD curve is as follows Figure 3 shown.

[0203] exist Figure 2 Select primary particles with better integrity, screen out primary particles that are not fully photographed at the edge of the picture, measure the longest length a and widest width b of each primary particle, and get the range of length a and width b respectively; then calculate the average length a and average width b, and finally calculate the average value of the absolute value of the relative deviation of length |Ma| and the average value of the absolute value of the relative deviation of width |Mb|. The test method is the same below.

[0204] Example 2

[0205] Compared with Example 1, this embodiment is different in that:

[0206] Step 1: Calculate and weigh nickel sulfate crystals and manganese sulfate crystals, and prepare a metal salt solution with a total metal molar amount of 2 mol / L according to the metal molar ratio of nickel and manganese of 88.5:11.5;

[0207] In step 4: after the reaction starts, the flow rate of the sodium hydroxide solution is adjusted to gradually reduce the pH to 10.5, and then the pH is gradually increased and maintained at 10.6-10.8. The difference in the pH drop and the final pH value maintained will result in differences in the width and length of the primary particles obtained.

[0208] The chemical formula of the precursor of the positive electrode material for lithium-ion batteries is Ni 0.885 Mn0.115 (OH)2.

[0209] The enlarged photo of the surface of the secondary particles of the obtained lithium-ion battery cathode material precursor is shown in Figure 4 As shown, the XRD curve is as follows Figure 5 shown.

[0210] Example 3

[0211] Compared with Example 1, this embodiment is different in that:

[0212] Step 1: Calculate and weigh nickel sulfate crystals, cobalt sulfate crystals, manganese sulfate crystals, and aluminum sulfate crystals, and prepare a metal salt solution with a total metal molar amount of 2 mol / L according to the metal molar ratio of nickel, cobalt, manganese, and aluminum of 88:3:7:2;

[0213] In step 4: the dehydrated nickel-cobalt-manganese-aluminum crystal nuclei with a D50 of 5 μm obtained in step 3 are put into a reactor, and water, sodium hydroxide solution and ammonia water are added to obtain a second bottom solution with a pH value of 10.6 and an ammonia concentration of 10.0 g / L. The metal salt solution, sodium hydroxide solution and ammonia water are continuously introduced into the reactor at a flow rate of 1.0-1.1% / h, 0.35-0.55% / h and 0.03-0.05% / h of the available reactor volume, respectively, at a constant temperature of 65°C. After the reaction starts, the pH is gradually increased to 11.0 by adjusting the flow rate of the sodium hydroxide solution, and then the pH is gradually decreased and finally maintained at 10.1-10.3. The different pH decreases and the pH values ​​finally maintained result in differences in the width and length of the primary particles obtained.

[0214] The chemical formula of the precursor of the positive electrode material for lithium-ion batteries is Ni 0.88 Co 0.03 Mn 0.07 Al 0.02 (OH)2.

[0215] The SEM partial magnified photo of the surface of the secondary particles of the obtained lithium-ion battery positive electrode material precursor is as follows: Figure 6 As shown, the XRD curve is as follows Figure 7 shown.

[0216] Comparative Example 1

[0217] The difference between this comparative example and Example 1 is that after the reaction starts in step 4, the flow rate of the sodium hydroxide solution is adjusted to gradually reduce the pH to 10.5, and then the pH is gradually increased and finally maintained at 11.1-11.3. The difference in the pH drop and the pH value finally maintained leads to differences in the width and length of the primary particles finally obtained.

[0218] The chemical formula of the obtained material is Ni 0.885 Co0.08 Mn 0.035 (OH)2.

[0219] The SEM partial magnified photo of the surface of the secondary particles of the obtained lithium-ion battery positive electrode material precursor is as follows: Figure 8 As shown, the XRD curve is as follows Fig. 9 shown.

[0220] Comparative Example 2

[0221] The difference between this comparative example and Example 1 is that in step 4: after the reaction starts, the flow rate of the sodium hydroxide solution is adjusted to gradually increase the pH and finally maintain it at a value of 11.4-11.6. The difference in the pH drop and the pH value finally maintained leads to differences in the width and length of the primary particles finally obtained.

[0222] The SEM partial magnified photo of the surface of the secondary particles of the obtained lithium-ion battery positive electrode material precursor is as follows: Fig.10 As shown, the XRD curve is as follows Fig.11 shown.

[0223] The present invention obtains the Ni of the composite structure 0.885 Co 0.08 Mn 0.035 (OH)2 material.

[0224] The test data of the precursor materials obtained in the embodiments and comparative examples are shown in Tables 1, 2 and 3 below:

[0225] Table 1 XRD data of precursor materials obtained in Examples and Comparative Examples

[0226]

[0227] Table 2 Primary particle data of precursor materials obtained in Examples and Comparative Examples

[0228]

[0229] Table 3 Other test data of precursor materials obtained in Examples and Comparative Examples

[0230]

[0231]

[0232] Cathode material preparation:

[0233] 2000 g of the precursor prepared in the embodiment and the comparative example and LiOH were mixed uniformly in a high-speed mixer at a molar ratio of 1:1.05, sintered in a box furnace under air atmosphere, and then crushed and sieved after cooling to room temperature to obtain a ternary positive electrode material.

[0234] Battery preparation:

[0235] The electrochemical performance test was conducted using a button-type semi-battery: the above-mentioned positive electrode materials, conductive carbon black, and binder PVDF (polyvinylidene fluoride) were mixed into a slurry according to a certain ratio, and then coated on aluminum foil to form a positive electrode sheet. The negative electrode sheet used a metal lithium sheet, and the electrolyte used 1mol / L LiPF6 / EC:DMC (volume ratio 1:1). The battery shell, positive and negative electrode sheets, diaphragms, springs, and gaskets were assembled into a button battery in a vacuum glove box. The electrochemical performance test was conducted using a blue electric test system.

[0236] The electrochemical data of the batteries obtained in the examples and comparative examples are shown in Table 4:

[0237] Table 4 Electrochemical data of the batteries obtained in the examples and comparative examples Note: 0.5C high temperature cycle efficiency (50th) (%) refers to the battery capacity retention rate after 50 cycles when the battery is charged and discharged at 0.5C at 45℃.

[0238] By comparing the above Examples 1, 2, 3 and Comparative Examples 1-2, the following conclusions can be obtained:

[0239] The products of different molecular formulas obtained in Examples 1-3 are all long strip or shuttle-shaped primary particles, and each XRD parameter is within the protection range, so that the precursor material has the (100) crystal plane and the (101) crystal plane as the dominant crystal planes, the crystallinity is high, the primary particles are consistent, and both capacity and cycle performance are taken into account.

[0240] Compared with Example 1, although the specific surface area BET of Comparative Example 1 is larger, it is beneficial for electrolyte penetration and improves capacity performance, but D (100) / D (001) The ratio is too low, the number of (101) crystals is too large, exceeding the limit, and the battery capacity is low under the combined influence. In addition, the length of the primary particles is too short, the width is too thin, and the morphology does not meet the requirements; FWHM (101) and D (101) / D (001) A small ratio may affect the crystal structure. During charging and discharging, the unit cell continuously expands and contracts, causing the positive electrode material particle structure to break and pulverize, ultimately showing poor cycle performance.

[0241] Compared with Example 1, although the XRD of Comparative Example 2 meets the (101) crystal number and D (100) / D (001) The numerical range requirements are met, but the primary particle morphology is blocky and the consistency is poor, showing a small specific surface area BET and a high tap density, which ultimately manifests as poor capacity and insignificant cycle differences.

[0242] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0243] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A lithium-ion battery positive electrode material precursor, characterized in that: The secondary particles of the precursor include a plurality of primary particles in strip or shuttle shape, and the precursor satisfies Formula 1, Formula 1: 1.50≤D (100) / D (001) ≤2.40, In formula 1, D (100) is the grain size in the (100) crystal plane, D (001) is the grain size in the (001) crystal plane.

2. The lithium-ion battery positive electrode material precursor according to claim 1, characterized in that: satisfying at least one of the following conditions: (1) The precursor satisfies Formula 2, Formula 2: 2.10≤D (100) / D (001) ≤2.30; (2) The precursor satisfies Formula 3, Formula 3: 2.00≤D (101) / D (001) ≤2.90, In formula 3, D (101) is the grain size in the (101) crystal plane, D (001) is the grain size in the (001) crystal plane; Preferably, the precursor satisfies Formula 4, Formula 4: 2.30≤D (101) / D (001) ≤2.70; (3) The full width at half maximum FWHM(101) of the (101) crystal plane of the precursor is 0.50° - 0.65°; (4) The diffraction peak intensity I of the precursor on the (101) crystal plane (101) The diffraction peak intensity I (001) Ratio I (101) / I (001) 0.97-1.10; (5) The precursor is in (101) wafer number N (101) 50-80, N (101) =D (101) / d (101) , d (101) represents the interplanar spacing of the (101) crystal plane; Preferably, the precursor is in (101) wafer number N (101) It is 60-70.

3. The lithium-ion battery positive electrode material precursor according to claim 1, characterized in that: satisfying at least one of the following conditions: ① The average value of the absolute value of the relative deviation 丨Ma丨 of the length of the primary particle ≤ 40%, and the average value of the absolute value of the relative deviation 丨Mb丨 of the width of the primary particle ≤ 40%, wherein, a is the length of the primary particle, and b is the width of the primary particle, is the average length of the primary particles, is the average width of the primary particles, 丨Ma丨 and 丨Mb丨 are calculated by Formula ① and Formula ② respectively, Official 1: Formula 2: ② The precursor includes The primary particles; Preferably, 4. The lithium-ion battery positive electrode material precursor according to any one of claims 1 to 3, characterized in that: satisfying at least one of the following conditions: A. The chemical formula of the precursor is Ni x M 1-x (OH)2, wherein 0≤x<1, and M is at least one of Co, Mn, Al, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb or Sr; Preferably, 0.6 ≤ x < 1; B. The chemical formula of the precursor is Ni y Co z M 1 w M 2 v (OH)2, where 0≤y<1, 0≤z<0.6, y+z+w+v=1; M 1 is Mn and / or Al; M 2 At least one of Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb or Sr; Preferably, 0.6 ≤ y < 1; C. The particle size D50 of the secondary particles of the precursor is 8 - 22 μm; D. The specific surface area of ​​the precursor is 8-20m 2 / g; Preferably, the BET specific surface area of ​​the precursor is 10-15 m 2 / g; E. The tap density TD of the precursor is 1.8-2.1 g / cm 3 .

5. A method for preparing a lithium-ion battery positive electrode material precursor according to any one of claims 1 to 4, characterized in that: including: Adding raw materials including a metal salt solution, a precipitant, and a complexing agent into a first bottom liquid, and performing a first reaction according to a first predetermined procedure until crystal nuclei are obtained; Adding materials including the metal salt solution, the precipitant, the complexing agent, and the crystal nuclei into a second bottom liquid, and performing a second reaction according to a second predetermined procedure until the precursor is obtained; wherein, each of the first bottom liquid and the second bottom liquid independently includes water, the precipitant, and the complexing agent.

6. The method for preparing a positive electrode material precursor for a lithium ion battery according to claim 5, characterized in that: satisfying at least one of the following conditions: a. The first predetermined procedure includes: after the start of the first reaction, gradually reducing the pH value during the first reaction process, and maintaining the final pH value of the first reaction within the range of 9 - 11; b. The second predetermined procedure includes: after the initial start of the second reaction, adjusting the pH value of the second reaction, and maintaining the final pH of the second reaction within the range of 10 - 12.

7. The method for preparing a positive electrode material precursor for a lithium ion battery according to claim 5 or 6, characterized in that: satisfying at least one of the following conditions: c. The particle size D50 of the crystal nuclei is 3 - 10 μm; d. The pH values of the first bottom liquid and the second bottom liquid are independently 10 - 12, and the ammonia concentrations of the first bottom liquid and the second bottom liquid are independently 1 - 15 g / L; e. During the first reaction process, the flow rate of the metal salt solution is 1 - 5% / h of the available volume of the reaction vessel, the flow rate of the precipitant is 0.35 - 1.85% / h of the available volume of the reaction vessel, and the flow rate of the complexing agent is 0.03 - 0.15% / h of the available volume of the reaction vessel; f. During the second reaction process, the flow rate of the metal salt solution is 1 - 5% / h of the available volume of the reaction vessel, the flow rate of the precipitant is 0.35 - 1.85% / h of the available volume of the reaction vessel, and the flow rate of the complexing agent is 0.03 - 0.15% / h of the available volume of the reaction vessel; g. The temperatures of the first reaction and the second reaction are independently 60 - 80°C; h. During the first reaction and the second reaction processes, the mother liquor is continuously discharged, and the discharge amount is equal to the total feed amount; i. After the second reaction is completed, post-processing is also included: the product of the second reaction is subjected to solid-liquid separation, drying, and sieving for demagnetization.

8. A positive electrode material for a lithium ion battery, characterized in that: The raw material of the positive electrode material includes the lithium ion battery positive electrode material precursor according to any one of claims 1 to 4.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery positive electrode material according to claim 8.

10. A lithium battery device, characterized in that: Includes the lithium ion battery as claimed in claim 9.

Citation Information

Cited By

  • Precursor for cathode active material, cathode active material, method for manufacturing precursor for cathode active material, cathode, and lithium secondary battery

    WO2026182593A1